ACEHNESE-SPEAKING PARENTS' CHOICE OF LANGUAGE OF THE CHILDREN: PARENTS' ATTITUDE TOWARDS BILINGUALISM IN ACEHNESE-INDONESIAN CONTEXT - Muhammad, Muna (Universitas Islam Negeri Banda Aceh, 2013)
Language shift is a notion on the change in the use of a person's heritage language that results in a loss of that person's ability to use his or her heritage language. Likewise, cultural shift is a change in participating in one's heritage culture that re-sults in a loss of understanding and adherence to one's cultural heritage. In her study, Withers suggests some factors that affect a shift in language and culture: the prestige of the dominant language and the comparatively lesser status of the herit-age language, the lack of societal support for the ethnic group and its heritage lan-guage, the perception of the heritage language as unnecessary by subsequent generations, a decrease of group identification through the heritage language, a low level of acquisition of the heritage language at the time of decreased use of that language, an increased amount of contact with the dominant culture, an increased use of the dominant language instead of the heritage language with children, and attitudes against keeping the heritage language.